Gain-of-Function Mutations in RARB Cause Intellectual Disability with Progressive Motor Impairment - Srour, Myriam; Caron, Véronique; Pearson, Toni; Nielsen, Sarah B.; Lévesque, Sébastien; Delrue, Marie-Ange; Becker, Troy A.; Hamdan, Fadi F.; Kibar, Zoha; Sattler, Shannon G.; Schneider, Michael C.; Bitoun, Pierre; et al. (Human mutation, 2016)
ABSTRACT Retinoic acid (RA) signaling plays a key role in the development and function of several systems in mammals. We previously discovered that the de novo mutations c.1159C>T (p.Arg387Cys) and c.1159C>A (p.Arg387Ser) in the RA Receptor Beta (RARB) gene cause microphthalmia and diaphragmatic hernia. However, the natural history of affected subjects beyond the prenatal or neonatal period was unknown. Here, we describe nine additional subjects with microphthalmia who have de novo mutations in RARB, including the previously described p.Arg387Cys as well as the novel c.887G>C (p.Gly296Ala) and c.638T>C (p.Leu213Pro). Moreover, we review the information on four previously reported cases. All subjects who survived the neonatal period (n = 10) displayed severe global developmental delay with progressive motor impairment due to spasticity and/or dystonia (with or without chorea). The majority of subjects also showed Chiari type I malformation and severe feeding difficulties. We previously found that p.Arg387Cys and p.Arg387Ser induce a gain‐of‐function. We show here that the p.Gly296Ala and p.Leu213Pro RARB mutations further promote the RA ligand‐induced transcriptional activity by twofold to threefold over the wild‐type receptor, also indicating a gain‐of‐function mechanism. These observations suggest that precise regulation of RA signaling is required for brain development and/or function in humans. We describe 9 subjects with microphthalmia who have de novo mutations in RARB (retinoic acid receptor beta), including the previously described p.Arg387Cys as well as the novel c.887G>C (p.Gly296Ala) and c.638T>C (p.Leu213Pro). Subjects have a complex neurologic phenotype characterised by severe developmental delay, progressive spasticity, movement disorder, Chiari‐I malformation and feeding difficulties. Additionally, we show that these mutations confer a gain of function. This study provides the first direct insight into the role of retinoid acid in the human brain.